Construction of efficient, tuber-specific, and cold-inducible promoters in potato. (June 2015) - Li, Meng; Xie, Conghua; Song, Botao; Ou, Yongbin; Lin, Yuan; Liu, Xun; Zhang, Huiling; Liu, Jun
Highlights: Efficient cold-inducible and tuber-specific promoters were constructed. We identified sequences that can optimise such promoters. The developed promoters are valuable for potato CIS regulation. The methodology can be applied to other biotechnological situations. Abstract: Promoter activity is crucial for precise gene expression. Previously, a synthetic tuber-specific and cold-inducible promoter, pCL, containing a C-repeat/dehydration-responsive element (CRT/DRE) cassette and a tuber-specific fragment, was constructed in order to regulate cold-induced sweetening (CIS) in potatoes. However, the utility of pCL is limited due to its low activity. To improve its inducibility in response to low temperatures, we modified the CRT/DRE and flanking sequences. In particular, promoter activity was significantly improved by site-specific mutation of flanking sequences next to the core element (CCGAC) of CRT/DRE. We also inserted a modified CRT/DRE cassette into pCL; although this enhanced activity, it was not more effective than mutation of the flanking sequences. Indeed, up to 20-fold enhanced pCL activity could be achieved by replacing the CRT/DRE cassette in pCL with tandem repeats of two mutated CRT/DRE cassettes. This improvement was due to an enhanced affinity between the CRT/DRE cassette(s) and the StCBF1 transcription factor. Together, these data suggest that altering the structure of CRT/DRE can enhance CBF-related transcription complex formation and thus improve the activity of this cold-inducible promoter.